Care provided by the nursing team in care of post-vaccination adverse events - Sidnéia Tessmer Casarin, Etiane Silveira Azambuja de Oliveira, Teila Ceolin, Deisi Cardoso Soares (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v5i2.5275